Fluororesin film, copper-clad laminate and substrate for circuits
A fluororesin film with controlled oxygen content and annealing treatment addresses lamination defects and adhesion issues, ensuring reliable bonding to copper foil for high-frequency circuit boards with reduced signal loss.
Patent Information
- Application Number
- JP2024187781
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-19
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2042-01-20
AI Technical Summary
Existing fluororesin films face challenges with defects during lamination and poor adhesion to copper foil, particularly in high-frequency circuit boards, due to residual stress and reduced oxygen content upon heating.
A fluororesin film with a specific oxygen element ratio of 1.35 atomic% or more, achieved through controlled heat treatment and surface modification, combined with annealing to relieve residual stress, ensuring minimal dimensional change and improved adhesion.
The solution reduces lamination defects and enhances adhesion to copper foil, maintaining low dielectric loss tangent for effective signal transmission in high-frequency applications.
Smart Images

Figure 2025003640000001 
Figure 2025003640000002 
Figure 2025003640000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fluororesin film, a copper-clad laminate, and a circuit board. [Background technology]
[0002] Epoxy resins and polyimide resins are widely used as insulating layers for circuit boards. In recent years, for high-frequency circuit boards used in applications in the high-frequency range of several tens of gigahertz, several configurations have been proposed in which an insulating layer of fluororesin is formed on copper foil from the viewpoints of dielectric properties and moisture absorption properties (Patent Documents 1 to 3).
[0003] In such printed wiring boards, the fluororesin film is sometimes subjected to a surface treatment to obtain adhesion to the copper foil (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2016 / 021666 [Patent Document 2] International Publication No. 2019 / 203243 [Patent Document 3] International Publication No. 2020 / 145133 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present disclosure is to provide a fluororesin film that reduces defects during lamination and has good adhesion to copper foil, and a copper-clad laminate using the same. [Means for solving the problem]
[0006] The present disclosure relates to A film made of a composition containing a fluororesin, After heat treatment at 180°C for 3 minutes, the oxygen element ratio is 1.35 atomic% or more when the surface condition of one or both sides is measured using a scanning X-ray photoelectron spectroscopy (XPS / ESCA). When the film is heat-treated at 180°C for 10 minutes, cooled to 25°C, and measured, the absolute value of the dimensional change rate in MD and TD before and after heat treatment is 2% or less. It is a fluororesin film.
[0007] The oxygen element ratio is preferably 1.5 atomic % or more. The fluororesin film preferably contains tetrafluoroethylene-perfluoroalkylvinylether (PFA) or tetrafluoroethylene-hexafluoropropylene (FEP).
[0008] The fluororesin film is It is preferable that the difference between the oxygen element ratio when the surface condition of one or both sides is measured by a scanning X-ray photoelectron spectroscopy (XPS / ESCA) and the oxygen element ratio when the film is etched in the depth direction for 15 minutes at an incidence angle of 45° with an argon gas cluster ion beam and then measured by a scanning X-ray photoelectron spectroscopy (XPS / ESCA) is 1.0 atomic % or more.
[0009] The above-mentioned fluororesin film preferably has an adhesive strength of more than 30 N / m on one or both sides when the films are attached to each other within the same plane at 200°C.
[0010] The fluororesin film preferably has a dielectric loss tangent at 10 GHz of less than 0.0015. The fluororesin film preferably has a dielectric loss tangent at 40 GHz of less than 0.0015. The number of unstable terminal groups in the above fluororesin film is 10, and the number of carbon atoms in the main chain of the fluororesin is 10. 6 Preferably, there are less than 10 per unit.
[0011] The fluororesin film preferably has an adhesive strength of 0.8 N / mm or more when adhered to a copper foil having a surface roughness Rz of 1.5 μm or less. The fluororesin film is preferably used for a copper-clad laminate.
[0012] The present disclosure also relates to a copper clad laminate having, as essential layers, a copper foil and any one of the above-mentioned fluororesin films. The copper clad laminate further has a layer other than the copper foil and the fluororesin film, The layers other than the copper foil and the fluororesin film are preferably at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether, and polybutadiene. The copper foil preferably has a surface roughness Rz of 1.5 μm or less. In the copper-clad laminate, the adhesive strength between the copper foil and the fluororesin film is preferably 0.8 N / mm or more.
[0013] The present disclosure also relates to a circuit board comprising any of the copper clad laminates described above.
[0014] The present disclosure also relates to a method for producing any of the copper clad laminates described above, characterized in that a fluororesin film is preheated to a temperature equal to or higher than the glass transition temperature and lower than the melting point of the film, and then a copper foil and / or a fluororesin film is laminated to a substrate other than a copper foil. Effect of the Invention
[0015] The fluororesin film of the present disclosure has the effect of reducing the occurrence of defects during lamination and also being able to obtain good adhesion to copper foil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present disclosure will now be described in detail. When manufacturing copper-clad laminates by roll-to-roll lamination of fluororesin film and copper foil, the challenges are to reduce defects in the lamination process and to obtain high adhesion between the fluororesin and copper foil. One of the causes of defects in the lamination process is that when a rolled film has wrinkles (tightening of the film), the film is laminated with the wrinkles still in place. This type of wrinkle (tightening of the film) is said to be caused by the film's shape changing over time in the rolled state.
[0017] Such changes in film shape over time are thought to be due to residual stress within the film, and possible methods to suppress this include carrying out an annealing treatment to relieve the residual stress in the fluororesin film, and adjusting manufacturing conditions such as melt extrusion conditions (e.g., T-die lip opening and air gap) and film winding conditions so that residual stress is less likely to remain during the film manufacturing process.
[0018] Furthermore, it is generally difficult for fluororesin to adhere to copper foil. For this reason, it is preferable to perform a surface treatment of the fluororesin film in order to improve the lamination properties. Generally, such a surface treatment is performed by increasing the amount of oxygen atoms on the resin surface.
[0019] It has been revealed that the effect of surface treatment of fluororesin film to improve adhesion tends to decrease by heating. This is presumably because oxygen atoms on the surface are released by heating, reducing the amount of oxygen atoms on the surface. In the lamination process, for example, the film is preheated to a temperature above the glass transition temperature and below the melting point before lamination to improve productivity. It has been revealed that in order for a fluororesin film that has been subjected to such a thermal history to have sufficient adhesion when bonded to copper foil, the oxygen atomic ratio must be 1.35 atomic % or more when the surface to be bonded to the copper foil is measured by a scanning X-ray photoelectron spectroscopy (XPS / ESCA) after heat treatment at 180°C for 3 minutes.
[0020] From the above perspective, (1) When the sample is heat-treated at 180°C for 10 minutes and then cooled to 25°C and measured, the absolute value of the dimensional change in MD and TD before and after heat treatment is 2.0% or less. and (2) After heat treatment at 180°C for 3 minutes, the oxygen atomic ratio on the surface to be bonded to the copper foil is 1.35 atomic% or more when measured using a scanning X-ray photoelectron spectroscopy (XPS / ESCA) device. By using a fluororesin film that simultaneously satisfies these two requirements, it is possible to obtain a fluororesin film that reduces defects during lamination and also has excellent adhesion to copper foil.
[0021] In order to obtain a fluororesin film that satisfies both of the above requirements (1) and (2), the conditions of the treatment process after molding the fluororesin film are important. As mentioned above, annealing can be mentioned as an example of a method for reducing the shrinkage rate to achieve the objectives of the present disclosure. Annealing of fluororesin films is generally a heat treatment. Therefore, when annealing is performed after surface treatment, the amount of oxygen atoms decreases, resulting in a decrease in adhesiveness. In addition, since the preheating process during lamination also reduces adhesiveness, when annealing is performed, it is necessary to select appropriate conditions for the surface treatment and annealing. In order to prevent such problems caused by annealing, a method of reducing internal stress by adjusting the film manufacturing process may be adopted. In the present disclosure, by adjusting the various conditions described above to obtain a fluororesin film that satisfies the above-mentioned (1) and (2), defects during lamination are reduced and good adhesion is obtained at the same time.
[0022] The present disclosure will be described in more detail below. The present disclosure relates to a fluororesin film. The resin constituting the fluororesin film here is not particularly limited, and may be a polymer containing fluorine atoms in part. The polymer containing fluorine atoms in part may be two or more types, and may contain other resins, rubbers, additives, fillers, etc. other than fluororesins. Furthermore, the fluororesin may contain at least one functional group selected from carbonyl group-containing groups (for example, acid anhydride groups, groups having carbonyl groups between carbon atoms of a hydrocarbon group, carbonate groups, carboxy groups, haloformyl groups, alkoxycarbonyl groups, etc.), hydroxy groups, epoxy groups, amide groups, amino groups, isocyanate groups, etc.
[0023] The method for introducing the functional group is not particularly limited, but for example, the functional group can be introduced during the production of the fluororesin. In this case, the functional group is derived from at least one selected from the group consisting of a monomer, a chain transfer agent, and a polymerization initiator used during the production. Examples of the monomer include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc. Examples of the chain transfer agent include those derived from methanol, acetic acid, acetic anhydride, methyl acetate, ethylene glycol, propylene glycol, etc. Examples of the polymerization initiator include ammonium persulfate, potassium persulfate, di-n-propyl peroxydicarbonate, diisopropyl peroxycarbonate, tert-butyl peroxyisopropyl carbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, etc.
[0024] The fluororesin is more preferably a melt-moldable fluororesin, and examples of such fluororesin include tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), copolymers having chlorotrifluoroethylene (CTFE) units (CTFE copolymers), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-ethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), chlorotrifluoroethylene-ethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), and polyvinyl fluoride (PVF), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer (THV), tetrafluoroethylene-vinylidene fluoride copolymer, and the like. Among these melt-moldable fluororesins, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) and tetrafluoroethylene-hexafluoropropylene copolymer (FEP) are preferred.
[0025] By using the above melt-moldable fluororesin, melt molding can be performed, so the processing cost can be reduced compared to the case of using PTFE. Furthermore, the adhesiveness when bonding with copper foil can be improved.
[0026] The resin constituting the fluororesin film preferably has a glass transition temperature of 40° C. or higher. A glass transition temperature of 40° C. or higher is preferable in that deformation at the environmental temperature is unlikely to occur, for example, when a roll film is stored at room temperature, and a glass transition temperature of 60° C. or higher is more preferable, and a glass transition temperature of 80° C. or higher is even more preferable. The upper limit is not particularly limited, but from the viewpoint of adhesion, a glass transition temperature of 200° C. or lower is preferable, a glass transition temperature of 160° C. or lower is more preferable, and a glass transition temperature of 120° C. or lower is even more preferable.
[0027] The melting point of the PFA is preferably 180 to 340° C., more preferably 230 to 330° C., and further preferably 280 to 320° C. The melting point is the temperature corresponding to the maximum value on the heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].
[0028] The PFA is not particularly limited, but is preferably a copolymer in which the molar ratio of TFE units to PAVE units (TFE units / PAVE units) is 70 / 30 or more and less than 99.5 / 0.5. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and an even more preferred molar ratio is 80 / 20 or more and 98.5 / 1.5 or less. If the TFE units are too few, the mechanical properties tend to decrease, and if the TFE units are too many, the melting point tends to become too high and moldability tends to decrease. The PFA may be a copolymer consisting of only TFE and PAVE, or it is also preferable that the monomer units derived from monomers copolymerizable with TFE and PAVE are 0.1 to 10 mol %, and the TFE units and PAVE units are 90 to 99.9 mol % in total. Examples of monomers copolymerizable with TFE and PAVE include HFP, CZ, and the like. 3 Z 4 =CZ 5 (CF 2 ) n Z6 (In the formula, Z 3 , Z 4 and Z 5 are the same or different and each represents a hydrogen atom or a fluorine atom; Z 6 represents a hydrogen atom, a fluorine atom or a chlorine atom, and n represents an integer of 2 to 10. 2 =CF-OCH 2 -Rf 7 (In the formula, Rf 7 represents a perfluoroalkyl group having 1 to 5 carbon atoms.) and alkyl perfluorovinyl ether derivatives represented by the formula (I) and (II). Other copolymerizable monomers include, for example, cyclic hydrocarbon monomers having an acid anhydride group, and examples of the acid anhydride monomers include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, and maleic anhydride. The acid anhydride monomers may be used alone or in combination of two or more.
[0029] The PFA preferably has a melt flow rate (MFR) of 0.1 to 100 g / 10 min, more preferably 0.5 to 90 g / 10 min, and even more preferably 1.0 to 85 g / 10 min. In this specification, the MFR is a value measured according to ASTM D3307 under conditions of a temperature of 372° C. and a load of 5.0 kg.
[0030] The FEP is not particularly limited, but is preferably a copolymer in which the molar ratio of TFE units to HFP units (TFE units / HFP units) is 70 / 30 or more and less than 99 / 1. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and an even more preferred molar ratio is 80 / 20 or more and 97 / 3 or less. If the TFE units are too few, the mechanical properties tend to decrease, and if the TFE units are too many, the melting point tends to become too high and the moldability tends to decrease. It is also preferred that the FEP is a copolymer in which the monomer units derived from a monomer copolymerizable with TFE and HFP are 0.1 to 10 mol %, and the total of the TFE units and HFP units is 90 to 99.9 mol %. Examples of the monomers copolymerizable with TFE and HFP include alkyl perfluorovinyl ether derivatives. Other copolymerizable monomers include, for example, cyclic hydrocarbon monomers having an acid anhydride group, and examples of the acid anhydride monomers include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc. The acid anhydride monomers may be used alone or in combination of two or more.
[0031] The melting point of the FEP is preferably 150 to 320° C., more preferably 200 to 300° C., and further preferably 240 to 280° C. The melting point is the temperature corresponding to the maximum value on the heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC]. The FEP has an MFR of preferably 0.01 to 100 g / 10 min, more preferably 0.1 to 80 g / 10 min, further preferably 1 to 60 g / 10 min, and particularly preferably 1 to 50 g / 10 min.
[0032] The fewer the functional groups, the better, and in particular the fewer the number of unstable terminal groups. Such fluororesins can be produced by adjusting the conditions during production (polymerization reaction), or by subjecting the fluororesin after polymerization to fluorine gas treatment, heat treatment, supercritical gas extraction treatment, or the like, thereby reducing the number of unstable terminal groups. This method has excellent processing efficiency, and the fact that some or all of the unstable terminal groups are -CF 3The fluorine gas treatment is preferable because it converts the fluorine end group to a stable terminal group. The use of a fluororesin having a reduced number of unstable terminal groups in this way is preferable because it reduces the electrostatic dissipation factor and the loss of an electrical signal.
[0033] The number of unstable terminal groups is not particularly limited, but is preferably 10 or more, more preferably 10 or more, most ... 6 The number per particle is preferably 450 or less, more preferably 250 or less, even more preferably 100 or less, and most preferably 50 or less. In consideration of the effect of reducing the dielectric tangent, the number per particle is preferably less than 10, and more preferably 5 or less.
[0034] The unstable terminal groups are specifically -COF, -COOH free, -COOH bonded, and hydroxyl groups (-CH 2 OH, etc.), -CONH 2 , -COOR(R=CH 3 etc.), -CF 2 Examples of functional groups include H and -OCOO-R (such as normal propyl carbonate).
[0035] Specifically, the number of unstable terminal groups is measured by the following method. First, the fluororesin is melted and compression molded to produce a film having a thickness of 0.25 to 0.3 mm. This film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the fluororesin, and a difference spectrum is obtained from a base spectrum in which the fluororesin is completely fluorinated and no functional groups are present. From the absorption peaks of specific functional groups that appear in this difference spectrum, the number of carbon atoms in the fluororesin is calculated according to the following formula (A): 6 The number of unstable terminal groups per unit is calculated. N=I×K / t (A) I: Absorbance K: Correction coefficient t: film thickness (mm)
[0036] For reference, the absorption frequency, molar absorption coefficient, and correction coefficient for the unstable terminal group in this specification are shown in Table 1. The molar absorption coefficient was determined from the FT-IR measurement data of a low molecular weight model compound.
[0037] [Table 1]
[0038] The fluorination treatment can be carried out by contacting a non-fluorination-treated fluororesin with a fluorine-containing compound.
[0039] The fluorine-containing compound is not particularly limited, but may be a fluorine radical source that generates fluorine radicals under fluorination treatment conditions. 2 Gas, CoF 3 , AgF 2 , U.F. 6 , OF 2 , N 2 F 2 , C.F. 3 OF, halogen fluorides (e.g. IF 5 , ClF 3 ) etc.
[0040] Above F 2 The fluorine radical source such as gas may be of 100% concentration, but from the viewpoint of safety, it is preferable to mix with an inert gas and dilute it to 5 to 50 mass %, more preferably to dilute it to 15 to 30 mass %. Examples of the inert gas include nitrogen gas, helium gas, argon gas, etc., and nitrogen gas is preferable from the viewpoint of economy.
[0041] The conditions for the fluorination treatment are not particularly limited, and the molten fluororesin may be brought into contact with the fluorine-containing compound, but the treatment is usually carried out at a temperature below the melting point of the fluororesin, preferably at 20 to 220°C, and more preferably at 100 to 200°C. The fluorination treatment is generally carried out for 1 to 30 hours, and preferably for 5 to 25 hours. The fluorination treatment is carried out by subjecting the unfluorinated fluororesin to fluorine gas (F 2 It is preferable to contact the gas with the
[0042] In this specification, the content of each monomer unit constituting the fluororesin can be calculated by an appropriate combination of NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.
[0043] The fluororesin film of the present disclosure may contain components other than the fluororesin. The components that can be contained are not particularly limited, and examples thereof include fillers such as silica particles and short glass fibers, and fluorine-free thermosetting resins and thermoplastic resins.
[0044] The composition containing the fluororesin of the present disclosure may contain spherical silica particles, which improves the flowability of the resin and makes it easy to mold even when a large amount of silica is blended.
[0045] The spherical silica particles refer to particles whose particle shape is close to a perfect sphere, and specifically, the sphericity is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and most preferably 0.95 or more. The sphericity is calculated by taking a photograph with an SEM and calculating the value from the area and perimeter of the observed particle as (sphericity) = {4π x (area) ÷ (perimeter) 2}. The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using an image processing device (Spectris Corporation: FPIA-3000) is used.
[0046] The spherical silica particles preferably have a D90 / D10 of 2 or more (preferably 2.3 or more, 2.5 or more) and a D50 of 10 μm or less when the volume is calculated from the smallest particle size. Furthermore, it is preferable that the D90 / D50 is 1.5 or more (more preferably 1.6 or more). It is preferable that the D50 / D10 is 1.5 or more (more preferably 1.6 or more). Since the small particle size spherical silica particles can enter the gaps between the large particle size spherical silica particles, it is possible to achieve excellent filling properties and high fluidity. In particular, it is preferable that the particle size distribution has a high frequency on the small particle size side compared to a Gaussian curve. The particle size can be measured by a laser diffraction scattering type particle size distribution measuring device. It is also preferable that coarse particles having a particle size of a predetermined size or more are removed by a filter or the like.
[0047] The spherical silica particles preferably have a water absorption of 1.0% or less, more preferably 0.5% or less. The water absorption is based on the mass of the silica particles when dry. The water absorption is measured by leaving a sample in a dry state at 40°C and 80% RH for 1 hour, and measuring the water generated by heating at 200°C using a Karl Fischer water content meter, and then calculating the water absorption.
[0048] Alternatively, the spherical silica particles can be prepared by heating the fluororesin composition at 600° C. for 30 minutes in an air atmosphere to burn off the fluororesin, and then extracting the spherical silica particles, after which the above-mentioned parameters can be measured using the above-mentioned method.
[0049] The silica powder of the present invention may be surface-treated. By previously performing the surface treatment, aggregation of the silica particles can be suppressed, and the silica particles can be well dispersed in the resin composition.
[0050] The surface treatment is not particularly limited, and any known surface treatment can be used.Specific examples include treatment with a silane coupling agent such as epoxysilane, aminosilane, vinylsilane, acrylicsilane, hydrophobic alkylsilane, phenylsilane, and fluorinated alkylsilane having a reactive functional group, plasma treatment, and fluorination treatment.
[0051] Examples of the silane coupling agent include epoxy silanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino silanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, vinyl silanes such as vinyltrimethoxysilane, and acrylic silanes such as acryloxytrimethoxysilane.
[0052] The spherical silica may be commercially available silica particles that satisfy the above-mentioned properties. Examples of commercially available silica particles include Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), Excelica (manufactured by Tokuyama Corporation), high-purity synthetic spherical silica Admafine (manufactured by Admatechs Co., Ltd.), Admanano (manufactured by Admatechs Co., Ltd.), and Admafuse (manufactured by Admatechs Co., Ltd.).
[0053] The film of the present disclosure has an oxygen atomic ratio of 1.35 atomic % or more when the surface condition of one or both sides is measured by ESCA after heat treatment at 180° C. for 3 minutes. The oxygen atomic ratio is more preferably 1.5 atomic % or more, even more preferably 1.8 atomic % or more, and most preferably 2.0 atomic % or more.
[0054] The film of the present disclosure may be a fluorine film in which the difference between the oxygen element ratio when the surface state is measured by a scanning X-ray photoelectron spectroscopy (XPS / ESCA) and the oxygen element ratio when the film is etched in the depth direction for 15 minutes with an argon gas cluster ion beam at an incidence angle of 45° and then measured by a scanning X-ray photoelectron spectroscopy (XPS / ESCA) is 1.0 atomic % or more. By increasing only the oxygen element ratio of the surface that contributes to adhesion in this way, sufficient adhesive strength can be obtained without impairing the dielectric properties.
[0055] The above heat treatment at 180°C for 3 minutes means that the film was placed on a metal tray and treated in an electric furnace in an air atmosphere.
[0056] The fluororesin film of the present disclosure has absolute values of MD and TD dimensional changes before and after heat treatment of 2.0% or less when heat treated at 180° C. for 10 minutes and then cooled to 25° C. and measured. The above dimensional change rate is more preferably 1.8% or less, and most preferably 1.5% or less. In this disclosure, the dimensional change rate is determined by dividing a film sample into 300 mm squares by 180 mm squares. The film was heat-treated for 10 minutes without load in an electric furnace set at 180℃ in an air atmosphere, and the gauge spacing in both the MD and TD directions was measured after cooling to 25℃, and the gauge spacing was calculated from the change in the gauge spacing before and after heat treatment.
[0057] The resin film of the present disclosure preferably has a dielectric loss tangent of less than 0.0015 at 10 GHz. By making it within this range, it is preferable in that the loss of electrical signals in the circuit can be suppressed. The dielectric loss tangent is more preferably less than 0.0013, even more preferably less than 0.0010, and most preferably 0.00050 or less. In addition, assuming that signal transmission and antenna transmission / reception will be performed at higher frequencies, the dielectric tangent at 40 GHz is preferably less than 0.0015, more preferably less than 0.0013, even more preferably less than 0.0010, and most preferably 0.00050 or less. In order to keep the dielectric loss tangent within the above range, it is preferable to use a resin having few unstable terminal groups, and it is more preferable to use a fluororesin that has been subjected to a terminal fluorination treatment.
[0058] The above-mentioned fluororesin film preferably has an adhesive strength of 0.8 N / mm or more, more preferably 0.9 N / mm or more, and even more preferably 1.0 N / mm or more, when bonded to a copper foil having a surface roughness Rz of 1.5 μm or less using a vacuum heat press under conditions of a temperature of from the melting point to the melting point +30° C., a pressure of 1.5 to 3.0 MPa, and a time of 300 to 600 seconds. The adhesive strength here means the adhesive strength measured under the conditions described in the Examples for the laminate bonded under the above conditions.
[0059] The fluororesin film preferably has an adhesive strength of more than 30 N / m on one or both sides when the films are bonded together within the same plane at 200° C. By having such an adhesive strength, the fluororesin film has excellent adhesiveness even after heat treatment when used in combination with various other substrates, and the adhesive strength is more preferably more than 50 N / m, and even more preferably more than 100 N / m.
[0060] (Fluororesin film manufacturing method) An example of a method for producing the above-mentioned fluororesin film of the present disclosure will be described in detail below. Note that the fluororesin film of the present disclosure is not limited to those produced by the following production method. The fluororesin film of the present disclosure is not particularly limited in the molding method for forming the film, but examples thereof include a melt molding method such as extrusion molding, a casting method in which a solution or dispersion containing a fluororesin is prepared, and then coated on a substrate and dried, etc. Furthermore, the film may be uniaxially or biaxially stretched, or may be an unstretched film.
[0061] The fluororesin film obtained by this method can be made to satisfy the above requirements (1) and (2) by subjecting one or both sides to a surface treatment and an annealing treatment under appropriate conditions.
[0062] The specific method for the surface modification is not particularly limited, and any known method can be used. The surface modification of the fluororesin film can be carried out by conventional discharge treatments such as corona discharge treatment, glow discharge treatment, plasma discharge treatment, and sputtering treatment. For example, the surface free energy can be controlled by introducing oxygen gas, nitrogen gas, hydrogen gas, etc. into the discharge atmosphere, and the surface to be modified can be exposed to an atmosphere of an organic compound-containing inert gas, which is an inert gas containing an organic compound, and a high-frequency voltage is applied between the electrodes to cause discharge, thereby generating active species on the surface, and then the functional group of the organic compound is introduced or a polymerizable organic compound is graft-polymerized to modify the surface. Examples of the inert gas include nitrogen gas, helium gas, and argon gas.
[0063] The organic compound in the organic compound-containing inert gas includes polymerizable or non-polymerizable organic compounds containing oxygen atoms, such as vinyl esters such as vinyl acetate and vinyl formate; acrylic esters such as glycidyl methacrylate; ethers such as vinyl ethyl ether, vinyl methyl ether, and glycidyl methyl ether; carboxylic acids such as acetic acid and formic acid; alcohols such as methyl alcohol, ethyl alcohol, phenol, and ethylene glycol; ketones such as acetone and methyl ethyl ketone; carboxylic esters such as ethyl acetate and ethyl formate; acrylic acids such as acrylic acid and methacrylic acid. Among these, vinyl esters, acrylic esters, and ketones are preferred because the modified surface is less likely to be deactivated, that is, because they have a long life and are easy to handle in terms of safety. In particular, vinyl acetate and glycidyl methacrylate are preferred.
[0064] The concentration of the organic compound in the organic compound-containing inert gas varies depending on the type of the organic compound, the type of fluororesin to be surface-modified, etc., but is usually 0.1 to 3.0% by volume, preferably 0.1 to 1.0% by volume, more preferably 0.15 to 1.0% by volume, and even more preferably 0.30 to 1.0% by volume. The discharge conditions may be appropriately selected depending on the desired degree of surface modification, the type of fluororesin, the type and concentration of the organic compound, etc. Usually, the discharge amount is 50 to 1500 W·min / m 2 , preferably 70 W·min / m 2 More than 1400W min / m 2The discharge treatment is carried out in the following range. The treatment temperature can be any temperature in the range of 0°C to 100°C. It is preferable that the temperature is 80°C or less because of concerns about stretching and wrinkling of the film. Considering that the adhesive ability of the surface is reduced due to heat during post-processing, the degree of surface modification is such that the abundance ratio of oxygen elements is 2.6% or more when observed by ESCA, preferably 2.8% or more, more preferably 3.0% or more, and even more preferably 3.5% or more. There is no particular restriction on the upper limit, but in consideration of the influence on productivity and other physical properties, it is preferable that it is 25.0% or less. There is no particular restriction on the abundance ratio of nitrogen elements, but it is preferable that it is 0.1% or more. The thickness of one fluororesin film is preferably 2.5 to 1000 μm, more preferably 5 to 500 μm, and even more preferably 12.5 to 150 μm.
[0065] In the production of the fluororesin film of the present disclosure, it is preferable to carry out an annealing treatment after carrying out the above-mentioned surface treatment. In addition, a heat treatment may be carried out in the process of laminating the film to another material such as copper foil. Therefore, the amount of oxygen on the surface of the fluororesin film decreases by undergoing these heat treatments. Therefore, it is preferable to carry out the surface modification under conditions that will obtain a sufficient amount of surface oxygen at the time when the fluororesin film is actually laminated to another material such as copper foil.
[0066] (Annealing treatment) The annealing treatment can be carried out by a heat treatment, for example, by passing the material through a heating furnace in a roll-to-roll manner.
[0067] The annealing temperature is preferably the glass transition temperature -20°C or more and less than the melting point, more preferably the glass transition temperature or more and less than the melting point -20°C or less, and even more preferably the glass transition temperature or more and less than the melting point -60°C or less. The annealing time is not particularly limited, but may be appropriately adjusted within a range of, for example, 0.5 to 60 minutes. In addition, if the film that has passed through the annealing furnace comes into contact with the roll of the winding device while still at a high temperature, the film is likely to deform (waviness) due to thermal contraction caused by temperature change. To prevent this, the film may be cooled by passing it through a cooling zone after the high-temperature annealing zone before being wound up by the winding device. The cooling method is not particularly limited, but it can be cooled with cold air or a cooling roll, and it is preferable that the film temperature is less than the glass transition temperature.
[0068] When heating is performed by the roll-to-roll method, the tension may be adjusted appropriately depending on the thickness of the film, the set temperature, etc., but is preferably 20 N / m or less. Heating under such conditions is preferable in that the internal stress can be sufficiently relaxed and no dimensional changes occur.
[0069] The order of the above surface treatment and annealing treatment is not particularly limited, and the number of times each step is performed is not limited to one, but may be two or more. Since tension is applied in the surface treatment step, it is preferable to perform the surface treatment before the annealing treatment in order to control the thermal shrinkage rate. In addition, the film may be slit to a predetermined width and length before or after these treatments, and in that case, it is preferable to adjust the tension so that the film does not stretch.
[0070] The fluororesin film of the present disclosure can be used as a sheet for printed wiring boards by laminating it with other substrates. The fluororesin film of the present disclosure preferably has a thickness of 2.5 to 1000 μm, more preferably 5 to 500 μm, and even more preferably 12.5 to 150 μm. The thickness can be selected in consideration of the balance between the electrical properties and linear expansion coefficient of the laminate.
[0071] The present disclosure also provides a laminate characterized by having copper foil adhered to one or both sides of the above-mentioned fluororesin film. As described above, the film containing the fluororesin of the present disclosure has excellent adhesiveness. The copper foil preferably has an Rz of 1.5 μm or less. That is, the fluororesin composition of the present disclosure also has excellent adhesiveness to copper foil having a high smoothness of Rz of 1.5 μm or less. Furthermore, the copper foil only needs to have a surface that is adhered to the above-mentioned fluororesin film of 1.5 μm or less, and the Rz value of the other surface is not particularly limited.
[0072] The thickness of the copper foil is not particularly limited, but is preferably in the range of 1 to 100 μm, more preferably in the range of 5 to 50 μm, and even more preferably in the range of 9 to 35 μm.
[0073] The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil.
[0074] The copper foil having Rz of 1.5 μm or less is not particularly limited, and commercially available products can be used. Examples of commercially available copper foil having Rz of 1.5 μm or less include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.).
[0075] The copper foil may be surface-treated to increase the adhesive strength with the fluororesin film of the present disclosure.
[0076] The surface treatment is not particularly limited, but may be a silane coupling treatment, a plasma treatment, a corona treatment, a UV treatment, an electron beam treatment, etc., and the reactive functional group of the silane coupling agent is not particularly limited, but from the viewpoint of adhesion to the resin substrate, it is preferable to have at least one selected from an amino group, a (meth)acrylic group, a mercapto group, and an epoxy group at the end. In addition, the hydrolyzable group is not particularly limited, but may be an alkoxy group such as a methoxy group or an ethoxy group. The copper foil used in the present disclosure may have an anti-rust layer (such as an oxide film such as chromate), a heat-resistant layer, etc. formed thereon.
[0077] The surface-treated copper foil having a surface treatment layer of the above-mentioned silane compound on the copper foil surface can be produced by preparing a solution containing the silane compound and then surface treating the copper foil with this solution.
[0078] The copper foil may have a roughening treatment layer on the surface thereof from the viewpoint of improving adhesion to a resin substrate. In addition, if there is a risk that the roughening treatment will degrade the performance required in the present disclosure, the amount of roughening particles electrodeposited on the copper foil surface can be reduced as necessary, or the roughening treatment can be omitted.
[0079] Between the copper foil and the surface treatment layer, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proofing treatment layer, and a chromate treatment layer may be provided in order to improve various properties. These layers may be a single layer or multiple layers.
[0080] The laminate preferably has an adhesive strength between the copper foil and the fluororesin film of 0.8 N / mm or more. Such an adhesive strength can be achieved by applying the method described above. By making the adhesive strength 0.9 N / mm or more, or even 1.0 N / mm or more, the laminate can be suitably used as a copper-clad laminate or a circuit board. The adhesive strength here means the adhesive strength measured under the conditions described in the examples. In addition, in the case of a laminate in which a copper foil is bonded to the surface-treated surface of a fluororesin film that has been surface-treated on only one side, a surface modification may be separately performed on the non-surface-treated surface of the fluororesin film in order to improve the adhesiveness between the laminate and other materials.
[0081] The present disclosure also relates to a laminate having a copper foil layer, the above-mentioned fluororesin film, and a base layer. The base layer is not particularly limited, but preferably has a fabric layer made of glass fiber and a resin film layer.
[0082] The glass fiber fabric layer is a layer made of glass cloth, glass nonwoven fabric, or the like. The glass cloth may be commercially available, and is preferably treated with a silane coupling agent to enhance affinity with the fluororesin. The glass cloth may be made of E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc., and is preferably made of E glass, S glass, or NE glass because of its easy availability. The fiber may be woven in either plain or twill weave. The thickness of the glass cloth is usually 5 to 90 μm, and preferably 10 to 75 μm, but it is preferable to use a glass cloth thinner than the fluororesin film to be used.
[0083] The laminate may use a glass nonwoven fabric as a fabric layer made of glass fibers. The glass nonwoven fabric is a fabric in which short glass fibers are fixed with a small amount of a binder compound (resin or inorganic substance), or a fabric in which the shape is maintained by entangling short glass fibers without using a binder compound, and a commercially available product can be used. The diameter of the short glass fibers is preferably 0.5 to 30 μm, and the fiber length is preferably 5 to 30 mm. Specific examples of the binder compound include resins such as epoxy resins, acrylic resins, cellulose, polyvinyl alcohol, and fluororesins, and inorganic substances such as silica compounds. The amount of the binder compound used is usually 3 to 15 mass % based on the short glass fibers. Examples of the material of the short glass fibers include E glass, C glass, A glass, S glass, D glass, NE glass, and low dielectric constant glass. The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm, and preferably 100 to 900 μm. In the present application, the thickness of the glass nonwoven fabric refers to a value measured in accordance with JIS P8118:1998 using a digital gauge DG-925 (load 110 grams, face diameter 10 mm) manufactured by Ono Sokki Co., Ltd. In order to increase the affinity with the fluororesin, the glass nonwoven fabric may be treated with a silane coupling agent.
[0084] Most nonwoven glass fabrics have a very high porosity of 80% or more, so it is preferable to use a sheet that is thicker than a sheet made of fluororesin and compress it by pressure.
[0085] The glass fiber fabric layer may be a layer in which a glass cloth and a glass nonwoven fabric are laminated together, whereby the properties of the two fabrics are combined to obtain suitable properties. The glass fiber fabric layer may be in the form of a prepreg impregnated with a resin.
[0086] In the above laminate, the glass fiber fabric layer and the fluororesin film may be bonded at the interface, or the glass fiber fabric layer may be partially or entirely impregnated with the fluororesin film. Furthermore, a prepreg may be prepared by impregnating a fabric made of glass fibers with a fluororesin composition. The prepreg thus obtained may be further laminated with the fluororesin film of the present disclosure. In this case, the fluororesin composition used in preparing the prepreg is not particularly limited, and the fluororesin film of the present disclosure may also be used.
[0087] The resin film used as the substrate is preferably a heat-resistant resin film or a thermosetting resin film. Examples of the heat-resistant resin film include polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, etc. Examples of the thermosetting resin include those containing epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether, polybutadiene, etc. The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but for example, glass cloth, particularly low dielectric type, is preferable. The heat-resistant resin film and the thermosetting resin film are not particularly limited in terms of dielectric properties, linear expansion coefficient, water absorption rate, and other properties, but for example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and even more preferably 3.0 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and even more preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, even more preferably 40 ppm / °C or less, and most preferably 20 ppm / °C or less. The water absorption rate is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less.
[0088] The fluororesin film of the present disclosure can be used in a laminate having a copper foil layer, a substrate layer, and the above-mentioned fluororesin film.
[0089] The method for combining the copper foil, the base layer, and the fluororesin film is not particularly limited, but the following two methods can be mentioned, for example. (i) A method of laminating copper foil, a base layer, and a preformed fluororesin film by applying pressure under heat using a roll-to-roll process or a press. (ii) A method in which a laminate is produced by adhering a fluororesin film to one side of a copper foil, and this is then laminated to a base layer by applying pressure under heat. In the case of the above method (ii), the laminate consisting of the copper foil, the base layer, and the fluororesin film may be surface-treated before bonding to other layers, or the surface of the fluororesin film to be bonded to the base layer may be surface-treated.
[0090] In these methods, when a copper clad laminate essentially comprising a fluororesin film and copper foil is laminated with a substrate layer such as a fabric layer made of glass fiber or a resin film layer, the copper clad laminate can be laminated by adhering the fluororesin film layer side to the substrate layer. In this case, the copper clad laminate may be used after a surface treatment is performed on the fluororesin film layer side thereof before lamination to improve adhesion performance. The surface treatment here is not particularly limited, and examples thereof include the above-mentioned plasma treatment.
[0091] In the above laminate, the order in which the copper foil layer, the base material layer, and the above-mentioned fluororesin film are laminated and the manufacturing method are not particularly limited, and a layer configuration according to the purpose can be adopted. Specific examples of the lamination order include a base material layer / fluororesin film / copper foil layer, a copper foil layer / fluororesin film / base material layer / fluororesin film / copper foil layer, and a copper foil layer / base material layer / fluororesin film / base material layer / copper foil layer. If necessary, other layers may also be included.
[0092] The copper foil in the laminate can be the same as the copper foil described in detail above in the laminate with the fluororesin film.
[0093] When obtaining the above-mentioned laminate configuration, the fluororesin film of the present disclosure is used by adhering copper foil to one or both sides. As described above, the fluororesin film of the present disclosure has excellent adhesiveness. Therefore, it also has excellent adhesiveness to copper foil having a high smoothness of Rz 1.5 μm or less. The adhesive strength between the copper foil and the fluororesin film is preferably 0.8 N / mm or more, and by making the adhesive strength 0.9 N / mm or more, and further 1.0 N / mm or more, it can be suitably used as a copper-clad laminate or a circuit board. The adhesive strength here means the adhesive strength measured under the conditions described in the examples.
[0094] Conventionally, copper foils used for circuit boards have been given a certain degree of unevenness on their surfaces to ensure adhesion to insulating layers. However, in high-frequency applications, the presence of unevenness on the surface of copper foil is undesirable because it causes electrical signal loss. The above laminate can obtain suitable adhesion even to copper foils with high smoothness, and is a laminate that can be suitably used as a circuit board.
[0095] The fluororesin film of the present disclosure has the effect of reducing the occurrence of defects during lamination and also providing good adhesion to copper foil. Since the fluororesin film has adhesion to copper foil with a high smoothness of Rz 1.5 μm or less, it can also provide a laminate that can be suitably used for copper-clad laminates, circuit boards, flat cables, coverlays, and the like.
[0096] In this disclosure, the high-frequency circuit does not only refer to a circuit that transmits only high-frequency signals, but also includes a circuit that has a transmission line that converts a high-frequency signal into a low-frequency signal and outputs the generated low-frequency signal to the outside, a transmission line for supplying power to drive high-frequency compatible components, and other transmission lines that transmit signals other than high-frequency signals, which are arranged on the same plane.The circuit can also be used as a circuit board for an antenna, a filter, etc. EXAMPLES
[0097] The present disclosure will be specifically described below based on examples, but the present invention is not limited to the following examples.
[0098] (Polymer Composition) Measured by 19F-NMR analysis.
[0099] (Melting Point) Calculated from the melting peak measured using a DSC device while heating at a rate of 10°C / min.
[0100] (glass transition temperature) Calculated from the tan δ peak measured using a solid dynamic viscoelasticity apparatus (DMA) at a frequency of 10 Hz, strain of 0.1%, and a temperature increase rate of 5°C / min.
[0101] (Melt Flow Rate (MFR) The measurements were performed in accordance with ASTM D3307 at a temperature of 372°C and a load of 5.0 kg.
[0102] (Thickness of fluororesin film) Measurements were taken using a micrometer.
[0103] (Number of unstable terminal groups) The analysis was carried out using an FT-IR Spectrometer 1760X (Perkin-Elmer).
[0104] (ESCA analysis of fluororesin film surface) The measurements were performed using a scanning X-ray photoelectron spectroscopy (XPS / ESCA) PHI5000VersaProbeII (ULVAC-PHI, Inc.).
[0105] (Dimensional change rate) A film sample was cut into a 300mm square, and gauge marks were placed at 180mm intervals in both the MD and TD directions. It was then placed on a metal plate covered with PTFE-impregnated glass cloth and heat-treated for 10 minutes in an electric furnace set to 180℃ in an air atmosphere without applying any load. After cooling to 25℃ (left to stand in a room at 25℃ for 30 minutes or more), the gauge intervals in both the MD and TD directions of the film were measured with a vernier caliper (unit: mm, can measure to two decimal places). The change in the gauge interval before and after heat treatment was used to calculate the following formula. Heat shrinkage rate = {(length after heat treatment - length before heat treatment) / length before heat treatment} x 100 (%)
[0106] (Wrinkles after annealing) Visually check for wrinkles 〇 No deformation (waviness) of the film ×: Film deformation (waving) occurs
[0107] (Wrinkles in roll film) After being wound into a roll, the product was stored at room temperature for one month, after which the appearance was visually evaluated. No increase or occurrence of wrinkles due to tightening ×: Creases occur or increase due to tightening.
[0108] (Copper foil surface roughness) The catalog values for electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.) were used.
[0109] (Adhesive strength between copper foil and fluororesin film) A fluororesin film was used, which was not preheated or was preheated at a temperature above the glass transition temperature but below the melting point, and the copper foil / fluororesin film / copper foil were laminated in that order. An aluminum plate was attached to one side of the laminate produced using a vacuum heat press with adhesive tape. A Tensilon universal testing machine (manufactured by Shimadzu Corporation) was then used to measure the peel strength of the copper foil by gripping and pulling a 10 mm wide piece of copper foil in a direction 90° to the plane of the laminate at a speed of 50 mm per minute, and the obtained value was taken as the adhesive strength.
[0110] (Adhesive strength between fluororesin films) The surface-treated sides of the fluororesin films were placed together and heat pressed (200°C, 0.1 MPa, 60 s) to create samples, which were then cut into 10 mm wide strips. Using a Tensilon universal testing machine (manufactured by Shimadzu Corporation), the unbonded parts of the strip samples were gripped between the top and bottom chucks of the Tensilon and pulled at a speed of 100 mm per minute to measure the peel strength, and the value obtained was taken as the adhesive strength.
[0111] (Dielectric constant and dielectric tangent of fluororesin film) Using a fluororesin film, measurements were performed at 10 GHz, 20 GHz, and 40 GHz (26°C) using split cylinder resonators CR-710 and CR-740 (EM Labs, Inc.), and the measurements were analyzed using a vector network analyzer P5007A (Keysight Technologies, Inc.).
[0112] (Sample 1) The type of fluororesin was PFA (TFE / PPVE copolymer, composition: TFE / PPVE = 95.8 / 4.2 (mass%), MFR: 15.8 g / 10 min, melting point: 305°C, number of unstable terminal groups: main chain carbon number 10 6 The film was melt-extruded by the T-die method and wound up into a long roll film with a thickness of 50 μm. Both sides of the film were then surface-treated (nitrogen gas containing 0.50% by volume of vinyl acetate was passed around the discharge electrode and roll-shaped ground electrode of a corona discharge device, and the film was passed continuously around the roll-shaped ground electrode, resulting in a discharge of 1324 W·min / m. 2 The film was subjected to corona discharge treatment on both sides and wound into a roll. The surface oxygen element ratio of the surface-treated film was 20.42% by ESCA surface analysis. The glass transition temperature of this film was 92°C.
[0113] (Sample 2) Discharge rate 265W·min / m 2A sample having a thickness of 50 μm and surface-treated on both sides was obtained in the same manner as in Sample 1, except that the oxygen element ratio was 11.64% by ESCA surface analysis.
[0114] (Sample 3) Discharge rate: 132 w·min / m 2 A sample having a thickness of 50 μm and surface-treated on both sides was obtained in the same manner as in Sample 1, except that the oxygen element ratio was 5.35% by ESCA surface analysis.
[0115] (Sample 4) Discharge rate 88W·min / m 2 A sample having a thickness of 50 μm and surface-treated on both sides was obtained in the same manner as in Sample 1, except that the oxygen element ratio was 3.66% by ESCA surface analysis.
[0116] (Sample 5) Discharge rate 66w·min / m 2 A sample having a thickness of 50 μm and surface-treated on both sides was obtained in the same manner as in Sample 1, except that the oxygen element ratio was 2.54% by ESCA surface analysis.
[0117] (Sample 6) A sample was obtained in the same manner as Sample 2, except that the type of fluororesin was fluorinated PFA (TFE / PPVE copolymer, composition: TFE / PPVE=95.8 / 4.2 (mass%), MFR: 16.2 g / 10 min, melting point: 305°C, number of unstable terminal groups: undetectable (less than 1 per 106 main chain carbon atoms)). The oxygen element ratio by ESCA surface analysis was 9.72%. The glass transition temperature of this film was 94°C.
[0118] The surface treatment conditions and surface analysis results of Samples 1 to 6 are shown in Table 2.
[0119] [Table 2]
[0120] Example 1 The film of sample 1 was passed through an annealing furnace (in an air atmosphere) at 180°C using the roll-to-roll method, the film was cooled in the cooling zone, and a long film was wound into a roll. At this time, the presence or absence of deformation (waviness) of the film after annealing was evaluated visually. Next, cut films sampled from this long roll film were placed in an electric furnace at 180°C and heat-treated for 10 minutes, and then cooled to room temperature. The dimensional change rates in the MD and TD directions were then measured, and their absolute values were calculated. In addition, the film wound around the core was stored at room temperature for one month, and the tightness of the winding was evaluated.
[0121] Example 2 Annealing was performed in the same manner as in Example 1, except that the film of Sample 2 was used, and the film was then evaluated for the presence or absence of deformation (waviness), and the dimensional change rate and tightness were measured.
[0122] Example 3 The annealing treatment was carried out in the same manner as in Example 2, except that the temperature of the annealing furnace was set to 200° C., and the film was then evaluated for the presence or absence of deformation (waviness), the rate of dimensional change was measured, and the tightness of the roll was evaluated.
[0123] Example 4 Annealing was performed in the same manner as in Example 1, except that the film of Sample 3 was used, and the presence or absence of deformation (waviness) of the film thereafter was evaluated, the dimensional change rate was measured, and the tightness of the roll was evaluated.
[0124] Example 5 Annealing was performed in the same manner as in Example 1, except that the film of Sample 4 was used, and the film was then evaluated for the presence or absence of deformation (waviness), and the dimensional change rate and tightness were measured.
[0125] Example 6 The annealing treatment was carried out in the same manner as in Example 1, except that the film of Sample 5 was used, and the presence or absence of deformation (waviness) of the film thereafter, the dimensional change rate was measured, and the tightness of the roll was evaluated.
[0126] Example 7 Annealing was performed in the same manner as in Example 1, except that the film of Sample 6 was used, and the film was then evaluated for the presence or absence of deformation (waviness), and the dimensional change rate and tightness were measured. Example 8 The annealing treatment was carried out in the same manner as in Example 1, except that no cooling zone was used in the annealing step. Thereafter, the film was evaluated for deformation (waviness), and the dimensional change rate and the tightness of the roll were measured.
[0127] Comparative Example 1 The annealing treatment was carried out in the same manner as in Example 2, except that the temperature of the annealing furnace was set to 250° C., and the film was then evaluated for the presence or absence of deformation (waviness), the dimensional change rate was measured, and the tightness of the roll was evaluated.
[0128] Comparative Example 2 The dimensional change rate of sample 2, which was not annealed, was measured and the tightening was evaluated.
[0129] The results of Examples 1 to 8 and Comparative Examples 1 and 2 are shown in Table 3.
[0130] [Table 3]
[0131] From the results in Table 3, it is possible to suppress tightening due to changes over time by adjusting the conditions of the annealing treatment and setting the absolute value of the dimensional change rate after heat treatment at 180°C for 10 minutes to 2% or less. Also, from Example 8, when a cooling zone was not included in the annealing process, the roll film after annealing was deformed (wavy) when unwound, and it was not possible to evaluate the tightening. In this state, defects will occur in the process of bonding with copper foil, etc., so it is preferable to include a cooling process in the annealing process.
[0132] Example 9 The film (sample 1:180) annealed in Example 1 was cut into 100 mm squares, placed on a metal tray, and placed in an electric furnace (air atmosphere) at 180 ° C. for 3 minutes for heat treatment. Using this film, the surface that was in contact with air during heat treatment was analyzed by ESCA. Next, the same surface of the heat-treated fluororesin film that was subjected to surface analysis was placed in contact with electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil and Powder Co., Ltd.), and bonded by heat pressing using a vacuum heat press machine (model number: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a press temperature of 320 ° C., a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressure time of 300 seconds, and peeled off at 90 ° with a Tensilon universal testing machine to measure the adhesive strength.
[0133] Example 10 The surface of the film (sample 2:180) annealed in Example 2 was analyzed by ESCA, and the oxygen element ratio was 8.15 atomic%. In addition, after etching in the depth direction for 15 minutes using an argon gas cluster ion beam at an incidence angle of 45° and sputtering conditions of 2.5 kV x 10 nA, the surface was analyzed by ESCA, and the oxygen element ratio was 0.88 atomic%. The difference between the two results was 7.27 atomic%. In addition, the adhesive strength between this annealed film and copper foil was 1.33 N / mm, and the adhesive strength between the film-treated surfaces was 250 N / m. Next, similar to Example 9, heat treatment at 180°C x 3 minutes, surface analysis, and measurement of adhesive strength were performed.
[0134] (Examples 11 to 12) Evaluation was performed in the same manner as in Example 9, except that the film annealed in Example 3 (Sample 2: 200) and the film annealed in Example 4 (Sample 3: 180) were used.
[0135] Example 13 The surface of the film (sample 4:180) annealed in Example 5 was analyzed by ESCA, and the oxygen element ratio was 2.67 atomic%. In addition, after etching in the depth direction for 15 minutes using an argon gas cluster ion beam at an incidence angle of 45° and sputtering conditions of 2.5 kV x 10 nA, the surface was analyzed by ESCA, and the oxygen element ratio was 0.90 atomic%. The difference between the two results was 1.77 atomic%. In addition, the adhesive strength between this annealed film and the copper foil was 1.27 N / mm. Next, similar to Example 9, heat treatment at 180°C x 3 minutes, surface analysis, and adhesive strength measurement were performed.
[0136] Example 14 The film was subjected to heat treatment at 180° C. for 3 minutes, and the surface analysis and adhesive strength measurement were carried out in the same manner as in Example 9, except that the film (sample 6:180) annealed in Example 7 was used.
[0137] Example 15 The film (sample 2:180) annealed in Example 2 was used and evaluated in the same manner as in Example 9, except that it was placed in an electric furnace (air atmosphere) at 120° C. and heat-treated for 3 minutes.
[0138] (Example 16) The film (sample 2:180) annealed in Example 2 was used and evaluated in the same manner as in Example 9, except that it was placed in an electric furnace (air atmosphere) at 200° C. and heat-treated for 3 minutes.
[0139] (Example 17) The film (sample 2:180) annealed in Example 2 was used and evaluated in the same manner as in Example 9, except that it was placed in an electric furnace (air atmosphere) at 250° C. and heat-treated for 3 minutes.
[0140] For Examples 10 and 14, the dielectric constant and dielectric loss tangent were measured using a split cylinder resonator (10 GHz and 40 GHz).
[0141] Comparative Example 3 The surface of the film (sample 5:180) annealed in Example 6 was analyzed by ESCA, and the oxygen element ratio was 1.78 atomic %. In addition, after etching in the depth direction for 15 minutes using an argon gas cluster ion beam at an incidence angle of 45° and sputtering conditions of 2.5 kV x 10 nA, the surface was analyzed by ESCA, and the oxygen element ratio was 0.86 atomic %. The difference between the two results was 0.92 atomic %. Next, similar to Example 8, heat treatment at 180°C x 3 minutes, surface analysis, and measurement of adhesive strength were performed.
[0142] The results of Examples 9 to 17 and Comparative Example 3 are shown in Table 4.
[0143] [Table 4]
[0144] Comparative Example 4 As in Sample 1, both sides of a 50 μm-thick film melt-extruded by the T-die method were surface-treated by discharge treatment without using an organic compound-containing inert gas. The film was passed through an annealing furnace (in an air atmosphere) at 180 ° C by roll-to-roll method, cooled in the cooling zone, and wound into a roll. The oxygen element ratio of the film surface after annealing was 4.16%. In addition, the adhesive strength between the treated surfaces of the film was 28 N / m. Next, as in Example 9, heat treatment at 180 ° C for 3 minutes, surface analysis, and measurement of adhesive strength with copper foil were performed. The oxygen element ratio of the film surface after heat treatment was 0.92%, and the adhesive strength with copper foil was 0.23 N / mm.
[0145] From the results in Table 4 and Comparative Example 4, by making the oxygen element ratio of the film surface after heat treatment at 180°C for 3 minutes 1.35 atomic % or more, an adhesive strength of 0.8 N / mm or more with copper foil can be obtained. In particular, in the case of surface treatment using an organic compound-containing inert gas of the present disclosure, deactivation by heat is less likely to occur, and it is preferably used. From the above, the fluororesin film of the present invention can obtain sufficient adhesive strength even if it is preheated in advance in a lamination process with copper foil and then laminated. In addition, since the dielectric loss tangent is 0.0015 or less, the transmission loss in the high frequency range of the circuit board can be reduced.
[0146] (Example 18) Fluorinated PFA (TFE / PPVE copolymer, composition: TFE / PPVE = 95.8 / 4.2 (mass%), MFR: 16.2 g / 10 min, melting point: 305°C, number of unstable terminal groups: undetectable (main chain carbon number 10 6 A sample was obtained by surface-treating one side of a 50 μm-thick film using the same method as in Sample 6, using 10.18% oxygen element ratio of the surface-treated surface as determined by ESCA surface analysis. The annealing treatment and dimensional change rate measurement in the MD and TD directions were performed using this film as in Example 7. The absolute values of the dimensional change rates were 0.90% in MD and 0.58% in TD. In addition, as in Example 14, the annealed film was placed on a metal tray so that the treated surface was in contact with air and heat-treated at 180°C for 3 minutes, and the surface-treated surface was analyzed by ESCA, resulting in an oxygen element ratio of 6.07%.
[0147] Next, the annealed film and electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil and Powder Co., Ltd.) were heat pressed using a vacuum heat press machine (model number: MKP-1000HVWH-S7 / manufactured by Mikado Technos Co., Ltd.) at a press temperature of 320 ° C, a preheating time of 60 seconds, a pressure of 1.5 MPa, and a pressurization time of 300 seconds to bond the surface-treated surface of the fluororesin film and the copper foil. The fluorofilm side of the obtained single-sided copper-clad laminate was surface-treated, and the laminate was laminated in the order of 1 single-sided copper-clad laminate / 2 prepregs R-5680 (GN) (thickness 132 μm) (manufactured by Panasonic Corporation) / 1 single-sided copper-clad laminate so that the surface-treated surface and the prepreg were aligned, and the laminate was bonded using a vacuum heat press machine at a press temperature of 200 ° C to obtain a double-sided copper-clad laminate. The adhesive strength between the copper foil and the fluorine film was 13.8 N / cm. The copper foil was removed from the double-sided copper-clad laminate, and the dielectric properties were measured at 20 GHz. The dielectric constant was 3.03 and the dielectric dissipation factor was 0.00208. The dielectric constant of a sample made by pressing only prepreg R-5680 (GN) (thickness 132 μm) (manufactured by Panasonic Corporation) at 200°C was 3.31 and the dielectric dissipation factor was 0.00244. The dielectric properties were measured at 40 GHz. The dielectric constant was 3.02 and the dielectric dissipation factor was 0.00252. The dielectric constant of a sample made by pressing only prepreg R-5680 (GN) (thickness 132 μm) (manufactured by Panasonic Corporation) at 200°C was 3.38 and the dielectric dissipation factor was 0.00294.
[0148] As seen from Example 18, by combining this fluororesin film with other materials, the electrical properties of the other materials can be improved, and by changing the thickness of the fluororesin film, it becomes possible to control the dielectric properties and other physical properties. In addition, since the thermal shrinkage rate is small and wrinkles are unlikely to occur, defects are unlikely to occur when laminating the fluororesin film and copper foil by roll-to-roll.
[0149] Considering the above experimental results as a whole, the fluororesin film of the present disclosure has the advantages of reducing defects during lamination, being able to be bonded to highly smooth copper foil, which has been difficult to achieve in the past, and having a low dielectric tangent, allowing for significant reduction in transmission loss when a laminate with highly smooth copper foil is used as a circuit board material. [Industrial Applicability]
[0150] The fluororesin film of the present disclosure can be suitably used for copper-clad laminates for circuit boards.
Claims
1. A laminate having a fluororesin film and a base layer, A laminate having a dielectric constant of less than 3.31 and a dielectric loss tangent of less than 0.00244 at 20 GHz.
2. 2. The laminate of claim 1, having a dielectric constant of less than 3.03 and a dielectric loss tangent of less than 0.00208 at 20 GHz.
3. A laminate having a fluororesin film and a base layer, A laminate having a dielectric constant of less than 3.38 and a dielectric loss tangent of less than 0.00294 at 40 GHz.
4. 4. The laminate of claim 3, having a dielectric constant of less than 3.02 and a dielectric loss tangent of less than 0.00252 at 40 GHz.
5. The laminate according to any one of claims 1 to 4, further comprising a copper foil layer.
6. 4. The laminate according to claim 1, wherein the substrate layer is a prepreg obtained by impregnating a fabric made of glass fibers with a fluororesin composition.
7. 4. The laminate according to claim 1, wherein the base layer is a layer containing at least one selected from the group consisting of polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, polyphenylene ether, and polybutadiene.
8. A copper-clad laminate comprising the laminate according to claim 1 or 3 and a copper foil.
9. A circuit board comprising the laminate according to claim 1 or 3.
10. A circuit board comprising the copper-clad laminate according to claim 8.
Citation Information
Patent Citations
Fluororesin film, copper-clad laminate and substrate for circuits
JP2022112028A
Fluororesin film, copper clad laminate and circuit board
JP2023022007A
Fluororesin film, manufacturing method for fluororesin film, sheet-like adhesive film for flexible copper-clad laminate, flexible copper-clad laminate and circuit board
JP2024121475A
Double-sided circuit substrate suitable for high-frequency circuits
WO2016021666A1
Roll film, method for producing roll film, method for producing copper-clad laminate, and method for producig printed wiring board
WO2019203243A1
Cited By
Semiconductor device
CN122373448A